2018
DOI: 10.1177/0003489418755407
|View full text |Cite
|
Sign up to set email alerts
|

One-Stage Complete Resection of Cholesteatoma With Labyrinthine Fistula: Hearing Changes and Clinical Outcomes

Abstract: Although caution is required for total removal of a large fistula, owing to increased risk of postoperative hearing deterioration, 1-stage complete resection of cholesteatoma matrix on labyrinthine fistula could be effective in disease control and long-term hearing preservation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Preservation of bone conduction hearing threshold in ears with residual hearing was attained in 97% of the smaller-fistula group and 71% of the larger fistula group. Rah et al 9 also found a significant difference between fistula size and postoperative bone conduction threshold. SNHL may occur due to the loss of inner ear function as a result of iatrogenic injuries when the matrix over the labyrinthine fistula is completely removed.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Preservation of bone conduction hearing threshold in ears with residual hearing was attained in 97% of the smaller-fistula group and 71% of the larger fistula group. Rah et al 9 also found a significant difference between fistula size and postoperative bone conduction threshold. SNHL may occur due to the loss of inner ear function as a result of iatrogenic injuries when the matrix over the labyrinthine fistula is completely removed.…”
Section: Discussionmentioning
confidence: 91%
“…All studies mentioned that a change of 10 dB or more in the bone conduction threshold was considered clinically significant. 1,5,[7][8][9] One of our cases had an average bone threshold conduction change of less than 10 dB at one month postoperative, which was considered as not clinically significant hearing deterioration based on the following literature. Ikeda et al 5 stated that poorer post operative bone conduction hearing was correlated with larger fistulae.…”
Section: Discussionmentioning
confidence: 94%
“…Among 947 patients affected by LF, a slight male prevalence was observed (pooled proportion, 55%; 95% CI, 51–59%; I 2 = 41%). Mean and median ages at diagnosis were quite heterogeneous, reported to be in the fourth decade by 7 studies (17,24,29,32,39,46,47), in the fifth by 9 (7,9,16,23,25,28,38,41,45), and in the sixth by 10 (10,11,26,27,31,33–35,37,43).…”
Section: Resultsmentioning
confidence: 99%
“…Although rather variable, canal wall down (CWD) or radical mastoidectomy were the most common procedures performed in most studies (2,9,10,(16)(17)(18)(24)(25)(26)(27)(28)(29)(30)(31)(32)(34)(35)(36)(37)(38)(39)(40)42,43,47), with a pooled proportion of 88% (95% CI, 79-94%; I 2 = 81%). LFs were most frequently located on the LSCC, with a pooled proportion of 90% (95% CI, 87-93%; I 2 = 46%).…”
Section: Characteristics Of Lfs and Surgical Managementmentioning
confidence: 99%
“…25 Moreover, observational studies have shown that perilymph leakage during removal of the matrix or a high rate of postoperative bone conduction hearing loss is more likely to be found with deeper fistulae. 12,15,[26][27][28] Thus, removal of the matrix overlaying deeper labyrinth fistulae is presumed to carry a greater risk of irreversible hearing deterioration.…”
Section: Discussionmentioning
confidence: 99%